Thermocatalytic Hydrogen Production Through Decomposition of Methane-A Review - Naikoo, Gowhar A.; Arshad, Fareeha; Hassan, Israr U.; Tabook, Musallam A.; Pedram, Mona Z.; Mustaqeem, Mujahid; Tabassum, Hassina; Ahmed, Waqar; Rezakazemi, Mashallah (Frontiers in Chemistry, 2021)
Consumption of fossil fuels, especially in transport and energy-dependent sectors, has led to large greenhouse gas production. Hydrogen is an exciting energy source that can serve our energy purposes and decrease toxic waste production. Decomposition of methane yields hydrogen devoid of COx components, thereby aiding as an eco-friendly approach towards large-scale hydrogen production. This review article is focused on hydrogen production through the thermocatalytic methane decomposition (TMD) for hydrogen production. The thermodynamics of this approach has been highlighted. Various methods of hydrogen production from fossil fuels and renewable resources were discussed. Methods including steam methane reforming, partial oxidation of methane, auto thermal reforming, direct biomass gasification, thermal water splitting, methane pyrolysis, aqueous reforming, and coal gasification have been reported in this article. A detailed overview of the different types of catalysts available, the reasons behind their deactivation, and the possible ways for their regeneration were discussed. We concluded the review by presenting the challenges and future hydrogen production perspectives via TMD.